Understanding Studies on Consumers’ Food Choices Using Food Choice Questionnaire: A Scoping Review and Bibliometric Analysis (ScoRBA) - Vieri Revaly Prasasta Sudewo; Suprehatin Suprehatin; Anisa Dwi Utami (Universitas Muhammadiyah Yogyakarta, 2023)
Since the development of the food choice questionnaire (FCQ) to assess consumers’ food choice motives in 1995, studies using the FCQ have been highly diverse. Despite the abundance of research on the topic, FCQ nevertheless manages to provide deep insights into consumers’ food choices—a crucial aspect for the agrifood industry and the formulation of food policies. This study aimed to analyze science mapping and synthesize research implications on the studies of consumers’ food choice motives using FCQ. In total, 169 FCQ-related journal articles were retrieved from the Scopus and Web of Science (WoS) databases for this study. The data were analyzed using a scoping review and bibliometric analysis (ScoRBA). The findings disclosed a positive trend in research on consumers’ food choice motives using FCQ. Notably, two seminal papers significantly influenced this field. Furthermore, specific research topics emerged and diversified over time, with recent themes encompassing consumer issues, consumer segments, research methods, and contextual factors. Recommendations for future research included: (1) conducting longitudinal studies to bridge the gap between food choice motives and dietary behaviors, with the incorporation of additional new recent factors; (2) longitudinal studies to explore nutrition, psychology, and health study groups in diverse cultural settings and more reliable research; (3) exploring FCQ research through a gender lens within varied cultural contexts, with an expansion of longitudinal research and more parameters; and (4) delving into FCQ research on adolescents, considering various potential influencing factors and utilizing data capable of elucidating causal relationships between variables.